Fiji land - Gill, Nick (Oberon modern plays., 2014)
In 2007, Ali Shalah, who had been a detainee at Abu Ghraib prison in Iraq, gave testimony about his torture there. In his statement, he referred to the part of the prison where prisoners were held: it was called "Fiji Land". Nick Gill's quite-hard-to-watch play is set in a prison where three military men watch over their detainees: several rows of pot plants